Ice Engineering. Number 24, January 2000. Ice-Affected Flood Frequency - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER NH (2000)
The Ice Engineering Information Exchange Bulletin is published as one of the information exchange functions of the Corps of Engineers. It is primarily intended to be a forum whereby information on ice engineering work done or managed by Corps offices, other U.S. Government agencies, and the engineering community in general. The purpose of the Bulletin is information exchange and not the promulgation of Corps policy. The analysis presented here addresses the development of ice-affect stage frequency. The methodology employed is within the general guidelines for ice-affected flooding as provided by the Federal Emergency Management Agency (FEMA 1995). Virtually every hydraulic structure design or other type of study involving rivers requires the development of a frequency analysis, in which river discharge is plotted against exceedance probability. These curves allow the quantitative selection of design life for structures such as bridges or levees, and are required for risk-based analyses. When combined with stage-discharge and stage-damage curves, damage estimates and other economic analyses can be made. Stage-frequency curves also are often the basis for regulatory floodplain delineation such as those presented in flood insurance studies. The original document contains color images.